Modeled interdependencies between intellectual capital, circular economy and economic growth in the context of bioeconomy - Alexandru-Mircea Nedelea; Marilena Mironiuc; Maria Carmen Huian; Mihaela Bȋrsan; Maria Viorica Bedrule-Grigoruţă (Amfiteatru Economic Journal, 2018)
The bioeconomy-specific paradigm has changed the perception of economic growth in the sense that the growth limits do not matter, but new growth opportunities. These are focused on: knowledge, investment in research, innovation and technological performance, which give meaning to the concept of smart economic growth;, green energy, low-carbon policies, reduced environmental collateral effects, which are attributes of sustainable economic growth. The paper dwells on the influence of bioeconomy on economic growth through an empirical study conducted between 2008 and 2015, using cross-sectional analysis applied to the interconnections between the data relative to the EU-28 member countries. Three econometric models, based on the Ordinary Least Square regression, have been developed to highlight the interdependencies between intellectual capital, circular economy and economic growth in the context of bioeconomy. The number of patents is the proxy variable designed to quantify innovative performance in the bioeconomic sectors, value added is the dependent variable that measures the achievements specific to the circular economy and gross domestic product quantifies the sensitivity of economic growth to the use of intangible resources (knowledge / intellectual capital) and of renewable resources used in cascade (specific to circular economy). The findings confirm the positive influence of research-development funding and of fiscal freedom on intellectual property rights materialized in patents. The added value created in circular economy responds well to recyclable raw material export, to population employment in circular economy and to municipal waste recycling rate. The productivity of bioeconomy employees positively influences economic growth in the EU-28. We also focused on negative aspects such as the poor results of innovation in relation to the allocated financing resources and the insufficient use of energy from renewable sources in the production process.
Keywords: O3; O1; O4; Q57; 330; bioeconomy; intellectual property; circular economy; economic growth; environmental performance